Estrategias para desarrollar la expresión oral en los estudiantes del nivel básico superior del colegio de bachillerato Hernán Gallardo Moscoso de la ciudad de Loja. Periodo académico 2014-2015. - Paz Acaro, Yessica Cristina (2016)
For the execution of the titled investigation work; STRATEGIES TO DEVELOP THE ORAL EXPRESSION IN THE STUDENTS OF THE LEVEL BASIC SUPERIOR OF THE COLLEGE GALLANT HERNÁN MOSCOSO OF THE CITY DE LOJA. ACADEMIC PERIOD 2014-2015, he thought about as general objective, to Contribute to the development of the oral expression in the students of the Level Basic Superior of the College Gallant Hernán Moscoso of the city of Loja. Academic period 2014-2015, for it was used it as methods: the scientist, descriptive, analytic-synthetic, inductive-deductive, each one applied in the stages corresponding to the work. The techniques were: the survey and the structured interview, as for the instruments; the questionnaire and the interview guide. The results obtained before the shop were negative, it was determined that the educational ones don't apply strategies to develop the oral expression, since they monopolize the work grope like macro strategy, with the application of the shop it was looked for to develop the oratorical one as strategy it bases, the results were satisfactory, the level of oral expression improved, this you evidences through the evaluation, the students discussed of the topics for the oratorical exercise, and also in the exhibition of the speech. In such a way that you concluded that the students develop expressive potential in the practice and in the participation of shops of oratorical, and that so much educational as students they should develop the oral expression periodically, for what is recommended to the educational one to upgrade the expression strategies that it applies with the students.